Dynamic distribution of gut microbiota in cattle at different breeds and health states - Wang, Lei; Wu, Daoyi; Zhang, Yu; Li, Kun; Wang, Mingjin; Ma, Jinping (Frontiers in Microbiology, 2023)
Weining cattle is a precious species with high tolerance to cold, disease and stress, which account for a large part of agricultural economic output in Guizhou China. However, the information about intestinal flora of Weining cattle is in a gap. In the research, high-throughput sequencing were employed to analyse the intestinal flora of Weining cattle (WN), Angus cattle (An) and diarrhea Angus cattle (DA), and explore the potential bacteria associated with disease resistance. We collected 18 manures in Weining, Guizhou, including Weining cattle, Healthy Angus and Diarrhoea Angus. The results of intestinal microbiota analysis showed there there were no significant differences in intestinal flora diversity and richness among groups (P<0.05). Nonetheless, the abundance of beneficial bacteria (Clostridia, Eubacterium Coprostanoligenes, Monoglobus, rumen bacterium, Muribaculaceae, Ruminobacter, Lachnospiraceae, Succinivibrionaceae and Veillonellaceae) were significantly higher than An group and DA group. The bacteria that threaten the health (Campylobacteria, Candidatus Soleaferrea) were enriched in DA group. Furthermore，the abundance of Lachnospiraceae was very high in WN group, which probably explains why the Weining cattle are less prone to diarrhea. This is the first report on the intestinal flora of Weining cattle, which helps to understand the relationship between intestinal flora and health.